Munkaerőpiaci sajátosságok vizsgálata az építőiparban - Sztányi, Róbert (Közép-Európai Közlemények, 2016)
Generations ago, many excellent specialists and prentices could be found. Since then, lack of experts has emerged as a result of the established economic situation and the rapid development. Based on analysis of changes in the building industry in Hungary, it is ascertainable that there are lot’s of factors which threaten the sustainability of the construction organizations. These factors are the following: developed lack of experts, the value of manual work, construction labor prestige, lack of education, quality of education. The main objective of my research is finding a connection between sustainability of construction organizations and the characteristics of the construction labor market. My other aim is exploring what competencies and skills must have a construction professionals to contribute to successful operation of the construction organizations with their performance.